PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT GEMILANG ABADI TELECOMINDO KARAWACI TANGERANG - Rian Sopana; Syawaludin Syawaludin (Jurnal Menara, 2025)
This study aims to find out how the influence of leadership style and organizational culture on employee performance at PT. Gemilang Abadi Telecomindo Karawaci Tangerang, to find out how leadership style influences employee performance at PT. Gemilang Abadi Telecomindo Karawaci Tangerang, to find out how organizational culture affects employee performance at PT. Gemilang Abadi Telecomindo Karawaci Tangerang. The method used in this study is a quantitative method, namely through approaches, data collection and analysis using statistics. A population of 150 employees with sample determination using the Slovin formula was obtained 109 samples. The data was used through observation, questionnaire and literature techniques. The analysis methods used in this study were validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, determination test and significant test (t test and F test). The results of the study show that leadership style has a positive and significant effect on employee performance, as seen from the t-test with a t-value of 12.541 > t-table 1.98 and Sig. 0.000 < 0.05. Partially, organizational culture has a positive and significant effect on employee performance, as seen from the t-test with a t-value of 13.380 > t-table 1.98 and Sig. 0.000 < 0.05. Simultaneously, leadership style and organizational culture have a positive and significant effect on employee performance, this can be seen from the results of the F test with F calculated 100.520 > F table 3.08 and Sig. 0.000 < 0.05, multiple linear regression obtained the equation Y = 6.113 + 0.446 X1 + 0.334 X2 with a multiple correlation coefficient of 0.809 and the adjusted R square determination coefficient is 0.648 or 64.8%.